Karakteristik Marshall Campuran AC-BC Dengan Menggunakan 6% Getah Damar Sebagai Bahan Substitusi Aspal - Kusmira Agustian; Muhammad Ridha (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
Construction of existing highways in Indonesia generally use flexible pavement, with the main material being asphalt. To increase the asphalt pavement resistance to the traffic load and the temperature is required asphalt modification one of them with substituted asphalt with resin sap. The purpose of this study was to see the impact of sap resin substitution into the asphalt pen. 60/70 to Marshall characteristics of AC-BC mixture. The first step of this research is to find the optimum bitumen content (KAO). After obtaining KAO then made the manufacture of the test object without and with the substitution of the percentage of resin sap percentage of 6% on the weight of the asphalt. From the results of research conducted found that the value of Density, VFA, and MQ decreased. While the value of VIM, VMA, and Flow has increased. At the value of Durability obtained at KOO 0% gum rosin of 97%, and increased in KOO 6% resin gum of 102%. For the Stability value of AC-BC with the substitution of resin sap decreased. Thus All marshall test methods with results obtained, other than VIM values have met the specification requirements by DGH 2010 revision 3 (2014).